Psychological Distress, Loneliness, and Boredom Among the General Population of Tyrol, Austria During the COVID-19 Pandemic - Tutzer, Franziska; Frajo-Apor, Beatrice; Pardeller, Silvia; Plattner, Barbara; Chernova, Anna; Haring, Christian; Holzner, Bernhard; Kemmler, Georg; Marksteiner, Josef; Miller, Carl; Schmidt, Martin; Sperner-Unterweger, Barbara; et al. (Frontiers in Psychiatry, 2021)
Background: COVID-19-related mental health problems are considered a public health challenge. The aim of this study was to investigate psychological distress, loneliness, and boredom among the general population of the federal state of Tyrol, Austria Methods: Residents of Tyrol aged ≥18 years were recruited via dissemination of a link through social media and other advertisements and invited to complete an online survey from June 26th to August 20th, 2020. Next to the collection of sociodemographic and COVID-19 related variables the Brief Symptom Checklist (BSCL), the Three-Item Loneliness Scale (TILS), and the Multidimensional State Boredom Scale-Short Form (MSBS-SF) were used to assess psychological distress, loneliness, and boredom. Results: 961 participants took part in the survey (68.3% woman). Of these, 14.4% were burdened from psychological distress (BSCL), 22.6% reached a TILS score ≥7 and were therefore classified as severely lonely, and boredom levels lay by a mean of 25.9±11.0 points in the MSBS-SF (range: 7-56). Women, singles, low-income people as well as those who were unemployed were significantly more often affected by all of the selected outcomes compared to the remaining sample and they had significantly more frequently consumed alcohol or other substances since the outbreak of the pandemic in order to feel better. In addition, young and middle-aged adults were particularly burdened by loneliness and boredom. Discussion: Our findings identify vulnerable groups and factors associated with higher psychological distress, loneliness, and boredom in the context of the pandemic. In order to prevent mental health problems it will be critical to identify options of maintaining social contacts and remaining active despite pandemic-related restrictions.